PENERAPAN MANAJEMEN BISNIS SYARIAH DALAM PEMANFAATAN KORAN BEKAS MENJADI PRODUK KERAJINAN DI DESA CIMANGGU SATU, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Ria Kusumaningrum; Susi Melinasari; Siti Neli Ismawati (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
Community service is one of the Tridharma functions of higher education, which aims to provide insight to the community to be able to innovate and work in managing waste of used newspapers into handicraft products. Comprehensive waste management can include reducing, reusing, and recycling which can change the value of worthless goods into products that have high selling value. This becomes more meaningful when applied to sharia business management. This community service activity will be carried out in 2020. The goal of this community service is to provide knowledge on how to use used newspapers to the people of Cimanggu Satu Village, Cibungbulang District, Bogor Regency. The method of implementing this community service is by counseling to and at the same time applying it to the people of Cimanggu Satu Village, Cibungbulang District, Bogor Regency. The community understands sharia business management, and has new skills in making handicraft products, such as making pencil cases or pens and flower vases.